MATRIK TRANSFORMASI PADA RUANG BARISAN ORLICZ - Haryadi Haryadi (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2022)
In this study will be characterized a matrix that maps the space of the Orlicz sequence space to the space of the bounded sequence and the convergence sequence. This study is carried out by generalized the matrix mapping on lp space, 1<=p<∞, to the Orlicz sequence space. This results establishes a necessary and sufficient conditions for a matrix that maps the Orlicz sequence space to the bounded sequence space, convergence to sequence space and the convergence sequence space.